Antibiotics Susceptibility Patterns Of Uropathogenic Bacteria Isolated From Patients With Community-Acquired Urinary Tract Infections, Kanifing General Hospital, The Gambia, 2021 - Kebbeh, A. (University Of Ghana, 2021)
Background: Urinary tract infection is a common infection affecting about 150 million people worldwide annually. Currently, the disease is becoming difficult to treat due to the emergence of resistant strains of uropathogenic bacteria. Bacterial resistance to antibiotics is a major public health concern resulting in treatment failure, leading to over 700,000 deaths yearly. The antimicrobial susceptibility pattern among uropathogenic bacteria for empirical decision making in treating UTI is unknown, at Kanifing General Hospital in The Gambia. This study determined the prevalence and risk factors associated with antibiotic susceptibility patterns of uropathogenic bacteria isolated from patients with Community-acquired UTI at Kanifing General Hospital in The Gambia. Methods: A cross-sectional study was conducted among Out-patients referred by attending clinicians to the laboratory to confirm UTI at the Kanifing General Hospital from March to May 2021. A purposive sampling method was used to recruit 422 study participants. Data on demographic characteristics and risk factors were collected from the patients using a case record form and structured questionnaires. A clean-catch mid-stream sample of urine was collected from study participants and analyzed after culture. The bacterial isolates identification was performed using standard microbiological methods and tested against various antibiotics using the Kirby Bauer disc diffusion method. Data were entered into an Excel sheet exported to the STATA Corp version. 16.1 for analysis. Data were analyzed using descriptive analysis, bivariate and multivariate logistic regression analysis at 95% confidence interval. Associations with p-values <0.05 were considered statistically significant. Results: The overall prevalence of UTI among patients clinically diagnosed with UTI was 12.8% (54/422) and females were most affected with a frequency of 14.7% (51/348). A total of five bacterial isolates were isolated from urine samples that yielded significant growth of bacteria. The most common bacteria isolated were E. coli 74.1% (40/54), followed by Klebsiella spp 18.5% (10/54). Resistance was highest for Erythromycin 96.3%(52/54), Ampicillin 87.0%(47/54), Trimethoprim/Sulfamethoxazole 77.8%(42/54) and Tetracycline 75.9%(41/54) antibiotics. Uropathogens sensitivity was 77.8% (42/54) for Nitrofurantoin and 75.9% (41/54) for ceftazidime. Imipenem and Meropenem were the most active antibiotics with a 100% susceptibility rate. The prevalence of multidrug-resistant among the bacteria isolated was 87.0% (47/54). Being female (aOR= 6.9,95% CI: 1.7-28.0), history of UTI (aOR= 2.6, 95% CI: 1.05-6.16), purchasing antibiotic from street vendor/local pharmacy (aOR= 2.0, 95% CI: 1.07-3.74) and having no formal education (aOR= 8.6, 95% CI: 1.1-67.1) were significantly associated with uropathogenic bacteria isolates (p-value < 0.05 ). Conclusion: Escherichia coli was the most prevalent bacteria and mostly identified among females. Nitrofurantoin, Ceftazidime, cefotaxime, cefoxitin, Imipenem and Meropenem were the most active antibiotics to the isolates. The identified uropathogenic bacteria show a high resistance to ampicillin, trimethoprim/sulfamethoxazole, erythromycin and tetracycline antibiotics. A high prevalence of MDR among the uropathogenic bacteria identified were also observed. Being female, having no formal education, history of UTI and buying antibiotics from street vendors or local pharmacy without medical prescription were significantly associated with uropathogenic bacterial isolates. Continuous AMR surveillance and monitoring are required to update clinical protocol of UTI management. We recommended community health education to reduce inappropriate use of antimicrobials.
MPhil. Applied Epidemiology And Disease Control
Keywords: Urinary Tract Infections; Uropathogens; Susceptibility Testing; Antimicrobial Resistance; The Gambia